Village Baseline Study: Site Analysis Report for Pailom village Champone district, Savannakhet province, Lao PDR (LA02) - Villanueva, Jerome; Soytavanh, Mienmany; Souvannaxayyavong, Chantha; Phonevisay, Silivong; Xayachack, S.; Keophoxay, Anousith; Khodyhotha, Khamphamy; Ferrer, Alice J.; Yen, B.T. (2015)
Data collection for the village baseline study of Pailom village located in Savannakhet Province, Lao PDR, took place from 17th -19th Oct, 2014. Focus group discussions were conducted separately for men and women. The village experienced yearly food shortage leading to hunger and malnutrition. Contributory factors included the frequent drought and crop damage from pests and diseases, poor irrigation facilities benefiting only very few farms, high concentration of salt in soil that limits crop diversification in certain areas of arable land, and increasing population that reduces the land area per person. Rice production was the main livelihood in the village but only limited during the wet season because it is mostly rainfall dependant. During the dry season, fields are left to fallow and used for livestock grazing. The government has provided emergency food aid such as rice and corn powder at subsidized cost during food shortage. , Villagers were temporarily migrating to Thailand to work as labourers in factories and in other farms. Few organizations were operating in the village, particularly working on food security and food crisis issues. Information networking for agricultural activities was mainly by individual (farmer to farmer) interaction rather than media. There was poor dissemination of agricultural information or technical support from agriculture extension workers and responsible agencies. Identified priorities in Pailom village include strengthening and promoting agricultural research extension to gather information on fertilizer management, sustainable agricultural production techniques, pest and disease management,